Metabolic Bone Disease: A Continued Challenge in Extremely Low Birth Weight Infants. (November 2014) - Viswanathan, Sreekanth; Khasawneh, Wasim; McNelis, Kera; Dykstra, Carly; Amstadt, Randi; Super, Dennis M.; Groh-Wargo, Sharon; Kumar, Deepak
Background: Metabolic bone disease (MBD) is an important prematurity-related morbidity, but remains inadequately investigated in extremely low birth weight (ELBW) infants, the group most at risk. The objective was to describe the incidence and associated risk factors of MBD in ELBW infants. Methods: Retrospective analysis of all ELBW infants admitted between January 2005 and December 2010 who survived > 8 weeks. MBD was defined as the presence of osteopenia or rickets in radiographs. Results: Of the 230 infants included in the study, 71 (30.9%) developed radiological evidence of MBD (cases) of which 24/71 (33.8%) developed spontaneous fractures. MBD and fractures were noted at mean postnatal ages of 58.2 ± 28 and 100.0 ± 61 days, respectively. Compared with controls, cases were smaller at birth (664.6 ± 146 g vs 798.1 ± 129 g), more premature (25.0 ± 1.8 vs 26.4 ± 1.9 weeks), more frequently associated with mechanical ventilation, chronic lung disease, parenteral nutrition days, cholestasis, furosemide, postnatal steroids, and antibiotics use (all P < .01). Cases had lower average weekly intake of calcium, phosphorous, vitamin D, protein, and calories during the first 8 weeks of life compared with controls. Cases with MBD, compared with controls, had higher mortality (14.1 vs 4.4%) and longer hospital stay (140.2 ± 51 vs 101.0 ± 42 days; P < .01). Conclusions: MBD remains an important morbidity in ELBW infants despite advances in neonatal nutrition. Further research is needed to optimize the management of chronic lung disease and early nutrition in ELBW infants.